Palaeoclimatic characteristics of the Late Jurassic-Cretaceous in Emei area, Sichuan Basin, China - Li, Shuxia; Xiang, Fang; Shao, Longyi; Zhao, Fenghua; Ma, Hewen; Xu, Bin; Sun, Shenkai (Frontiers in Earth Science, 2025)
The Late Mesozoic is a typical period for studying the greenhouse climate and the interaction of the Eearth’s systems. To expound the interaction between the evolution process of the terrestrial surface system and the environment in the Late Jurassic -Cretaceous, a typical profile with relatively complete exposure of the Mesozoic strata in the Emei area of the Sichuan Basin, the Chuanzu Profile, was selected for this study. The sedimentary environment of the study area was qualitatively analysed based on the macroscopic characteristics of the lithostratigraphy of outcrop profiles in the field and the statistical data of detrital composition under a microscope. Factor analysis and the chemical alteration index after correction (CIAcorr) were used to quantitatively analyse the characteristics of major and trace elements. Finally, the palaeoclimatic evolutionary characteristics of the Late Jurassic-Cretaceous in the Emei area are systematically discussed. The results show that the formation of Cretaceous sediments in the Emei area of the Sichuan Basin is mainly controlled by climatic factors, but is little affected by tectonic activities, and the maturity of the rock clastic composition is relatively low; therefore, it should be a near-provenance deposit. The range of CIAcorr values was 55–79, indicating that the degree of chemical weathering of the provenance was weak to moderate. The palaeoclimate in the Late Jurassic gradually became humid from Early to Late; in the Early Cretaceous, it was semiarid to semihumid, with an extremely dry event occurring; and in the Late Cretaceous, it was semiarid and drier than that of the Early Cretaceous.